2013
DOI: 10.1160/th12-11-0791
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein-related peptidases (KLKs) in gastrointestinal cancer: Mechanistic and clinical aspects

Abstract: SummaryThe human tissue kallikrein (KLK1) and kallikrein-related peptidases (KLKs) are secreted serine proteases with diverse expression patterns and physiological roles in different systems, including the digestive system. The aberrant expression of KLKs in gastrointestinal malignancies as well as their implication in carcinogenesis including cell growth regulation, angiogenesis, invasion, and metastasis, has prompted scientists to investigate their potential as cancer biomarkers. Expression of distinct KLKs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 55 publications
2
41
0
Order By: Relevance
“…KLK11 is significantly downregulated at both mRNA and protein levels in GC tissues and appears to be an independent marker of superior DFS and OS (Unal et al 2013). Regarding KLK13, is downregulated in GC tissues compared to their normal counterparts and its expression is associated with less GC aggressive features and improved DFS and OS (Kontos et al 2013). Recent results revealed that KLK13 expression is modulated in cultivated GC cell lines, after their exposure to different antineoplastic agents, suggesting that KLK13 may be employed as a treatment-response predictor for GC (Florou et al 2012).…”
Section: Klks With Potential Clinical Utility In Gastric Cancermentioning
confidence: 99%
See 4 more Smart Citations
“…KLK11 is significantly downregulated at both mRNA and protein levels in GC tissues and appears to be an independent marker of superior DFS and OS (Unal et al 2013). Regarding KLK13, is downregulated in GC tissues compared to their normal counterparts and its expression is associated with less GC aggressive features and improved DFS and OS (Kontos et al 2013). Recent results revealed that KLK13 expression is modulated in cultivated GC cell lines, after their exposure to different antineoplastic agents, suggesting that KLK13 may be employed as a treatment-response predictor for GC (Florou et al 2012).…”
Section: Klks With Potential Clinical Utility In Gastric Cancermentioning
confidence: 99%
“…Colorectal cancer (CRC) remains one of the three most frequently diagnosed malignancies in both genders, despite the recent achievements in resection procedures and chemotherapy (Kontos et al 2013). As a consequence, the identification and establishment of novel biomarkers for GC and CRC is necessary for optimal clinical management of these patients.…”
Section: Gastric and Colon Cancermentioning
confidence: 99%
See 3 more Smart Citations